ANN modeling of nickel base super alloys for time dependent deformation - Al Hazza, Muataz Hazza Faizi; Hassan, Muhammad Hasibul (Engineering and Technology Publishing, 2014)
Alloys 617 and 276 are nickel-based super alloys with excellent mechanical properties, oxidation, creepresistance,